Cosmic Bulk Flow Analysis in Modified Gravity Theories: f(R) and Perturbed f(R) Models with Neutrino Coupling - Muhammad Yarahmadi; Amin Salehi (The Astronomical Journal)
In this study, we explore the characteristics of bulk flow across various redshift ranges within the frameworks of f ( R ) gravity, perturbed f ( R ) gravity, and perturbed f ( R ) gravity coupled with neutrinos. Our investigation reveals profound insights into large-scale cosmic flows and their interactions with major cosmic structures, such as the Sloan Great Wall (SGW) and the King Ghidorah Supercluster (KGSc). We find that incorporating neutrinos into the perturbed f ( R ) gravity model results in a substantial increase in bulk flow velocities across all redshifts, with notable enhancements in the higher redshift ranges, where velocities can exceed 3000 km s ^−1 in the 0.8 <  z  < 1.4 range. Moreover, the direction of the bulk flow in this model closely aligns with the dark energy dipole, especially at redshifts z  > 0.4, showing near-perfect congruence with cosmic superclusters. This suggests a significant interaction between neutrinos and cosmic structures, influencing cosmic acceleration. At lower redshifts, such as 0.1 <  z  < 0.2, the bulk flow aligns with the SGW, while in the 0.4 <  z  < 0.6 range it aligns with the KGSc. In the low redshift range 0.001 <  z  < 0.016, although velocities are lower, neutrinos still subtly increase the bulk flow velocity and maintain alignment with nearby cosmic structures, such as the Local Supercluster. Our results underscore the critical role of neutrinos in shaping cosmic flows and offer new insights into the interplay between dark energy, neutrinos, and modified gravity models. Future research should delve deeper into these interactions to elucidate the mechanisms influencing large-scale cosmic structures.